Clinical outcomes of robotic-assisted laparoscopic partial nephrectomy with renal hypothermia perfusion by renal artery balloon catheter in treating patients with complex renal tumors - Bai, YuChen; Yang, YunKai; Wei, HaiBin; Quan, Jing; Wei, Fei; Zhang, Qi; Liu, Feng (Frontiers in Oncology, 2022)
Objective To investigate the safety and efficacy of renal hypothermic perfusion by renal artery balloon catheter during robot-assisted laparoscopic partial nephrectomy (P-RALPN) for patients with complex renal tumor. Materials and methods We retrospectively identified 45 patients with complex renal tumor received standard robot-assisted laparoscopic partial nephrectomy (S-RALPN) and 11 patients treated with P-RALPN from September 2017 to October 2021. Preoperative patients’ characteristics, intraoperative surgical parameters including operating time, blood loss, hospitalization, pre- and post-surgical glomerular filtration rate (GFR), and postoperative survival time were compared between two groups. The patients’ body temperature, real-time kidney temperature and short-term renal functional were analyzed in P-RALPN group. Results There were no statistically significant difference on median intraoperative estimated blood loss and postoperative hospitalization between two groups. Notably, patients received P-RALPN had the slightly longer operative time than those received S-RALPN (P = 0.09). The volume of perfusion solution was 533.2 (range 255.0-750.0) ml and median temperature of kidney was 22.6 (range 21.7-24.1) ℃ after kidney cooling down. The median minimum intraoperative temperature of patients was 36.1 (range 35.2-36.7) ℃. Interestingly, the ischemia time of S-RALPN group was lower than P-RALPN group (P<0.01). However, the loss of GFR was much higher in P-RALPN group than in S-RALPN group after the surgery (P=0.01). Importantly, patients had similar postoperative survival time between two groups.(hazard ratio = 0. 27, P = 0.415). Conclusion P-RALPN is a safe and feasible surgery in the treatment of patients with complex renal tumors, which provides a new operative approach for clinicians to treat these patients.